Homocoupling of aryl halides in flow: Space integration of lithiation and FeCl3 promoted homocoupling - Nagaki, Aiichiro; Uesugi, Yuki; Tomida, Yutaka; Yoshida, Jun-ichi (Beilstein Journal of Organic Chemistry, 2011)
The use of FeCl3 resulted in a fast homocoupling of aryllithiums, and this enabled its integration with the halogen–lithium exchange reaction of aryl halides in a flow microreactor. This system allows the homocoupling of two aryl halides bearing electrophilic functional groups, such as CN and NO2, in under a minute.
Keywords: homocoupling; iron salts; microreactor; organolithiums